Strategi Peningkatan Kualitas Layanan Gizi RSU Nurhayati Garut dan Pengembangan sebagai Profit Center - Shofia Salsabila; Minto Yuwono (CV Edujavare Publishing, 2025)
Nutrition services in hospitals play an important role in supporting patient recovery, but are still faced with challenges such as high food waste and lack of patient diet follow-up. This study aims to analyze the feasibility of nutrition services at RSU Nurhayati Garut as a profit center through a mix method approach with concurrent triangulation design. Data were collected from 10 internal informants and 82 inpatients, and analyzed using the Canvas Business Model, SWOT analysis, and SERVQUAL approach to assess service quality. The results show that RSU Nurhayati has the potential to develop nutrition services into a financially independent unit through the provision of healthy catering and digital-based nutrition consultations. The service quality score reached 78.88% which is classified as good. The proposed development strategies include HR training, product innovation, service digitalization, market segment expansion, and operational efficiency. This study concludes that with proper strategic planning, RSU Nurhayati's nutrition services can be improved in quality while being developed as a source of hospital income.